One-Step Nucleic Acid Amplification Analysis of Sentinel Nodes in Endometrial Cancer Versus Ultrastaging: First Long-Term Follow-Up Data of Discordant Cases - Kosťun, Jan; Ismail, Khaled M; Pešta, Martin; Slunečko, Robert; Stráník, Petr; Smoligová, Vendula; Presl, Jiří (Cancer reports, 2024)
AIMS: Endometrial cancer (EC) is the most common gynecological cancer worldwide and its incidence is rising. The cornerstone of its management is surgical treatment with nodal staging. A monocentric study investigating the potential of the molecular biology method of one-step nucleic acid amplification (OSNA) in sentinel lymph node (SLN) analysis was conducted at our institution between April 2016 and January 2018. Histopathological ultrastaging was used as the reference standard for SLN examination and OSNA as the index test. The aim of this study was to assess the long-term outcome of patients with discordant SLN and OSNA results. To our knowledge, this is the first study exploring this issue. METHODS AND RESULTS: Patients were followed in line with the current ESMO/ESGO/ESTRO recommendations. The institutional electronic database was retrospectively searched for patients' follow-up data from April 2016 till March 2023. Only patients who provided a written valid consent and had a positive OSNA and negative ultrastaging of their SLN analysis were included in the study. The primary endpoint was the retrospective analysis of their clinical outcome. Data from 58 patients enrolled into our previous study were reviewed and 12 discordant patients who met the inclusion criteria for this study were identified. The median follow-up was 83 months. Disease recurrence was detected in 3 (25%) patients, two of these were nodal and both patients died. One patient had a solitary lung metastasis which was surgically treated, and the patient was disease-free during the whole study period. CONCLUSION: The recurrence rate of patients included in the study was in the intermediate-high and high-risk group range, and hence, higher than expected based on ultrastaging results. Furthermore, benign epithelial inclusions do not seem to adversely affect OSNA SLN analysis in EC patients.
Keywords: dospělí; Sentinel Lymph Node Biopsy; senioři nad 80 let; Endometrial Neoplasms; retrospektivní studie; Humans; staging nádorů; následné studie; lokální recidiva nádoru; lidé středního věku; Middle Aged; Neoplasm Staging; techniky amplifikace nukleových kyselin; Aged, 80 and over; Follow-Up Studies; sentinelová uzlina; Sentinel Lymph Node; nádory endometria; Neoplasm Recurrence, Local; Adult; lymfatické metastázy; Lymphatic Metastasis; ženské pohlaví; lidé; Nucleic Acid Amplification Techniques; biopsie sentinelové lymfatické uzliny; Aged; senioři; Retrospective Studies; Female